2007 IEEE International Symposium on Power Line Communications and Its Applications 2007
DOI: 10.1109/isplc.2007.371117
|View full text |Cite
|
Sign up to set email alerts
|

Turbo-Fuzzy Equalization for Single-Carrier Power Line Channels

Abstract: Abstract-This paper introduces a turbo-fuzzy equalizer (TFEQ) to cope with the inter-symbol interference effects and impulsive noise occurrences in bandlimited digital communication channels, such as the indoor and outdoor power line circuits. We exploit a close relationship between the fuzzy and Bayesian equalizers to derive an adaptive nonsingleton turbo-fuzzy equalization technique. Generally speaking, the TFEQ is obtained by introducing an adaptive decision feedback nonsingleton fuzzy equalizer into the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In PLC systems, nonlinear equalizers such as radial basis function (RBF) networks and fuzzy equalizers [5]- [8] are also favorable choices, and several studies have demonstrated their good performances in the presence of serious uncertainty posed by the pulse noise.…”
Section: Introductionmentioning
confidence: 99%
“…In PLC systems, nonlinear equalizers such as radial basis function (RBF) networks and fuzzy equalizers [5]- [8] are also favorable choices, and several studies have demonstrated their good performances in the presence of serious uncertainty posed by the pulse noise.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional channel equalizers, including transversal equalizers, decision feedback equalizers (DFE) and maximumlikelihood sequence equalizers (MLSE), are optimized under Gaussian noise. In PLC systems, nonlinear equalizers such as radial basis function (RBF) networks and fuzzy equalizers [5]- [8] are also favorable choices, and several studies have demonstrated their good performances in the presence of serious uncertainty posed by the pulse noise.…”
Section: Introductionmentioning
confidence: 99%